A Calculus for Direct Deduction with Dominance Constraints - Jaspars, Jan; Koller, Alexander (Proceedings of the Amsterdam Colloquium, 1999)
Underspecification has become a popular approach to dealing with ambiguity. An important operation in this context is direct deduction, deduction on underspecified descriptions which is justified by the meaning of the described formulae. We instantiate an abstract approach to direct deduction to dominance constraints, a concrete underspecification formalism, and obtain a sounds and complete calculus.